2013
DOI: 10.1111/phn.12043
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Hmong Women's Beliefs, Feelings, Norms, and External Conditions About Breast and Cervical Cancer Screening

Abstract: Consistent with the TCSB, Hmong women's beliefs, affect, cultural norms and external conditions helped to understand their use of breast and cervical screening. Findings could guide nursing and public health interventions to improve culturally sensitive, cancer screening for Hmong women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(75 citation statements)
references
References 27 publications
(35 reference statements)
4
69
0
Order By: Relevance
“…In addition, cancer itself is an unfamiliar concept to Hmong people, making it more difficult for physicians to explain the rationale behind each screening (Lor & Bowers 2014). This study adds to the current literature because we provide information about physicians’ perspectives regarding barriers and facilitators to screening and demonstrate how the factors they identified are very similar to those previously identified by LEP patients (Akers et al 2007; Watts et al 2009; Fang & Baker 2013; Lor et al 2013). Additionally, we propose a multifactorial model that includes patient, physician, interpreter and system level facilitators or barriers as a way of organizing and conceptualizing these barriers (Figure 1).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In addition, cancer itself is an unfamiliar concept to Hmong people, making it more difficult for physicians to explain the rationale behind each screening (Lor & Bowers 2014). This study adds to the current literature because we provide information about physicians’ perspectives regarding barriers and facilitators to screening and demonstrate how the factors they identified are very similar to those previously identified by LEP patients (Akers et al 2007; Watts et al 2009; Fang & Baker 2013; Lor et al 2013). Additionally, we propose a multifactorial model that includes patient, physician, interpreter and system level facilitators or barriers as a way of organizing and conceptualizing these barriers (Figure 1).…”
Section: Discussionsupporting
confidence: 53%
“…The literature also suggests that culture is an important influence to patients’ beliefs about cancer screening. In a study of Hmong women’s beliefs about breast and cervical cancer screenings, Lor et al found that Hmong women encountered cultural barriers such as embarrassment undressing for an exam and listening to authority figures (2013). In addition, cancer itself is an unfamiliar concept to Hmong people, making it more difficult for physicians to explain the rationale behind each screening (Lor & Bowers 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many other studies in Africa [12, 14] and in female immigrants and minority groups in the United States [20, 21] found this to also be a common theme in women’s lack of awareness regarding screening. Many studies also cited reasons related to husbands not giving consent for screening [12, 2227] which was very marginal in our study, with only one participant out of the 351 having mentioned this reason as a barrier to her screening for cervical cancer. Other barriers were fear of being diagnosed with cancer, neglect and distance from the screening center.…”
Section: Discussionmentioning
confidence: 69%
“…In the Hmong culture, there is a strong sense of modesty and embarrassment related to body parts and the intrusiveness of gynecologic exams [3, 6, 7]. Fear of discovering they have cancer has also been shown to prevent Hmong women from seeking cancer screening [6, 11]. …”
Section: Introductionmentioning
confidence: 99%